Young Children Feeding Practices: An Update from the Sultanate of Oman - Salima Al Maamari; Saleh Al Shammakhi; Ibtisam Alghamari; Jana Jabbour; Ayoub Al-Jawaldeh (MDPI AG, 2021)
Despite proven benefits, most countries fail to meet international targets for appropriate complementary and Breast Feeding (BF) practices. This study assessed feeding practices of children under two years of age and correlated them with family parameters in Oman, a high income country in the Eastern Mediterranean Region. Methods: Data from this study originated from the latest Oman National Nutrition Survey (ONNS). Assessment of children and their mothers' socioeconomic, anthropometric, and nutritional variables was conducted at the household level. Evaluated feeding practices included age appropriate BF, diet diversity, and minimum acceptable diet (MAD). Results: Pairs of mothers and infants (n = 1344) were assessed. Early BF, exclusive BF at 6 months, infant formula, and iron rich meals were provided to 81, 29, 44, and 84% of children, respectively. Age appropriate BF and MAD were found in 58% and 35% of children, respectively. Low maternal education, younger age, low household income, and governorate negatively affected diet acceptability. Conclusion: Omani children successfully received early BF postpartum and consumed iron rich meals. Yet, rates of exclusive BF rates at six months and MAD for children under two were low. Comprehensive strategies should be placed to assess and influence children feeding practices in the Sultanate.